PENGEMBANGAN BAHAN AJAR BERBASIS SAINTIFIK PADA TEMA CUACA DI KELAS III SEKOLAH DASAR - Nurmairina, Dinda; Dinda Arianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to: (1) To produce the development of scientific-based teaching materials on the theme of weather in grade III of elementary school. (2) To analyze the feasibility of scientific-based teaching materials that will be developed on the theme of weather in grade III of elementary school. Which is based on the lack of student response and student interest in reading during the learning process, this causes difficulties in understanding integrated thematic learning. This study is a type of Research and Development (R&D) research. This study was developed using five steps of the ADDIE development model, including: 1) Analyze, 2) Design 3) Development, 4) Implementation, 5) Evaluation. Data collection techniques used were interviews, observations and questionnaires. Quantitative and qualitative data were analyzed using a Likert scale. This study produced scientific-based teaching materials on the theme of weather in grade III of elementary school with the material